Strengthening Upstream Forest Conservation Policies to Achieve Sustainable Development Goals - Absori, Absori; Trias Hernanda; Rizka, Rizka; Bangsawan, Mohammad Indra; Budiono, Arief (Lembaga Contrarius Indonesia, 2025)
Existing studies on watershed and forest conservation in the upstream Bengawan Solo region have largely focused on ecological degradation, technical conservation strategies, or regulatory shortcomings. However, there remains a significant gap in understanding how an ecoregion based approach can be systematically integrated with local wisdom to produce a comprehensive and context specific conservation policy. The study investigates the role of local wisdom in upstream forest management, the existence of gaps in legal protection for watershed conservation, and the impact of integrating local wisdom with legal frameworks on policy effectiveness. An empirical method with a qualitative approach was employed, drawing on primary data obtained through field observations in four regencies, namely Wonogiri, Sukoharjo, Surakarta, and Karanganyar. The results of this study reveal three principal findings. First, sustainable conservation in the upstream Bengawan Solo watershed requires a synergistic model that integrates ecological considerations with community based knowledge systems. Second, fragmented regional regulations and weak legal coordination continue to obstruct effective watershed governance, resulting in inconsistent conservation practices across administrative boundaries. Third, the study highlights the need for comprehensive policy reform through the establishment of interregional cooperation mechanisms supported by a Memorandum of Understanding, which can strengthen institutional governance, harmonize conservation strategies, and enhance long term ecological resilience within the watershed area.